Effect of aryl orientation on olefin polymerization in iminopyridyl catalytic system. (18th June 2020) - Dai, Shengyu; Li, Shuaikang
Abstract: Herein, synthesis and characterization of a series of bulky aryl substituted iminopyridyl ligands and the corresponding palladium and nickel complexes are described in detail. The as-synthesized palladium complexes show moderate activity in the ethylene polymerization and generate highly-branched oligoethylene or polyethylene with low molecular-weights. Meanwhile, the prepared palladium complexes perform a high degree of comonomer incorporation in ethylene/methyl acrylate (MA) or ethylene/acrylic acid (AA) copolymerizations. Exclusively, Pd3 catalyst exhibits a high comonomer incorporation and provides copolymers with an appreciable molecular weight for ethylene/MA (8.4 MA%, 12937 g mol −1 ) and ethylene/AA (8.9 AA%, 12552 g mol −1 ). The corresponding nickel complexes are all highly active in ethylene polymerization and produce branched oligoethylene and/or polyethylene with low to moderate molecular weights. Intriguingly, the orientation of aryl substituents plays a decisive role in the molecular weight of the attained polymer or copolymer under the performed reaction conditions. Graphical abstract: Image 1 Highlights: Proper orientation of the aryl group makes ethylene oligomerization to polymerization. Synthetize high polar monomer incorporation copolymers with high molecular weight. Preparation of polar functionalized polyethylene oil with various molecular weights.